Outcomes Following Possible Undiagnosed Aneurysmal Subarachnoid Hemorrhage: A Contemporary Analysis. (18th September 2017) - Mark, Dustin G.; Kene, Mamata V.; Vinson, David R.; Ballard, Dustin W.
Abstract: Objectives: Existing literature suggests that patients with aneurysmal subarachnoid hemorrhage (aSAH) and "sentinel" aSAH symptoms prompting healthcare evaluations prior to aSAH diagnosis are at increased risk of unfavorable neurologic outcomes and death. Accordingly, these encounters have been presumed to be unrecognized opportunities to diagnose aSAH and the worse outcomes representative of the added risks of delayed diagnoses. We sought to reinvestigate this paradigm among a contemporary cohort of patients with aSAH. Methods: A case‐control cohort was retrospectively assembled among patients diagnosed with aSAH between January 1, 2007 and June 30, 2013 within an integrated healthcare delivery system. Patients with a discrete clinical evaluation for headache or neck pain within 14 days prior to formal aSAH diagnosis were identified as cases, and the remaining patients served as controls. Modified Rankin Scale scores at 90 days and 1 year were determined by structured chart review. Multivariable logistic regression controlling for age, sex, ethnicity, presence of intracerebral or intraventricular hemorrhage at diagnosis, and aneurysm size was used to compare adjusted outcomes. Sensitivity analyses were performed using varying definitions of favorable neurologic outcomes, a restricted control subgroup of patients with normal mental status at hospital admission, inclusion of additional cases that were diagnosed outside of the integrated health system, and exclusion of patients without evidence of subarachnoid blood on initial noncontrast cranial computed tomography (CT) at the diagnostic encounter (i.e. "CT‐negative" SAH). Results: A total of 450 patients with aSAH were identified, 46 (10%) of whom had clinical evaluations for possible aSAH‐related symptoms in the 14 days preceding formal diagnosis (cases). In contrast to prior reports, no differences were observed among cases compared to control patients in adjusted odds of death or unfavorable neurologic status at 90 days (0.35, 95% confidence interval [CI] = 0.11–1.15; 0.59, 95% CI = 0.22–1.60, respectively) or at 1 year (0.58, 95% CI = 0.19–1.73; 0.52, 95% CI = 0.18–1.51, respectively). Likewise, neither restricting the analysis to a control subgroup of patients with normal mental status at hospital admission, varying the dichotomous definition of unfavorable neurologic outcome, inclusion of cases diagnosed outside the integrated health system, or exclusion of patients with CT‐negative SAH resulted in significant adjusted outcome differences. Conclusion: In a contemporary cohort of patients with aSAH, we observed no statistically significant increase in the adjusted odds of death or unfavorable neurologic outcomes among patients with clinical evaluations for possible aSAH‐related symptoms in the 14 days preceding formal diagnosis of aSAH. While these findings cannot exclude a smaller risk difference than previously reported, they can help refine decision analyses and testing threshold determinations for patients with possible aSAH.